2009
DOI: 10.1177/2156759x0901300203
|View full text |Cite
|
Sign up to set email alerts
|

Using Leader-Member Exchange Theory to Examine Principal–School Counselor Relationships, School Counselors’ Roles, Job Satisfaction, and Turnover Intentions

Abstract: Principals have considerable influence on shaping the role of school counselors with whom they work (Amatea & Clark, 2005; Dollarhide, Smith, & Lemberger, 2007; Ponec & Brock, 2000). Researchers used leader-member exchange theory (Graen & Uhl-Bien, 1995) to examine the relevance of principal–school counselor relationships to school counselors’ role definition, job satisfaction, and turnover intentions. A path analysis model explained 15% of the variance in how school counselors’ roles are defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 14 publications
3
32
0
1
Order By: Relevance
“…This finding seems plausible considering prior researcher has found that the principal/SC relationship influences the extent to which SCs are used to their greatest capacity (Clemens et al, 2009). The next most commonly reported barrier to program implementation was time, which also is consistent with previous research (Cervoni & DeLucia-Waack, 2011;Zalaquett, 2005).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This finding seems plausible considering prior researcher has found that the principal/SC relationship influences the extent to which SCs are used to their greatest capacity (Clemens et al, 2009). The next most commonly reported barrier to program implementation was time, which also is consistent with previous research (Cervoni & DeLucia-Waack, 2011;Zalaquett, 2005).…”
Section: Discussionsupporting
confidence: 55%
“…The authors found principals most often envisioned SCs being primarily responsible for administrative tasks such as managing student records, coordinating tests, and monitoring 504 plans (Bickmore & Curry, 2013). This is particularly concerning considering principals are responsible for assigning tasks to school personnel, which can influence how SCs develop their professional identity (Chata & Loesch, 2007;Clemens et al, 2009). …”
Section: School Leaders' Perceptions Of School Counselorsmentioning
confidence: 99%
“…Factors related to increased school counselor service delivery are examined throughout the literature. Clemens and colleagues () found that the principal–school counselor relationship ( N = 188) and use of counselor advocacy skills contributed to the implementation of services. Furthermore, Shillingford and Lambie () found that school counselors’ ( N = 163) leadership practices (e.g., the activities conducted to secure support of others toward the organizational goal) contributed to their frequency of service delivery; however, counselors’ values (e.g., the guiding principles in one's life) did not contribute to service delivery.…”
Section: School Counselors’ Programmatic Service Delivery and Self‐efmentioning
confidence: 99%
“…Factors that impede school counselors’ facilitation of student services are identified, including (a) fear of failing or inadequacy (Dollarhide, Gibson, & Saginak, ); (b) limited counselor acceptance of roles within comprehensive school counseling (Dahir, Burnham, & Stone, ); (c) role conflict and ambiguity (DeMato & Curcio, ); (d) high student‐to‐counselor ratios (ASCA, ; Lapan, Gysbers, Stanley, & Pierce, ); (e) time spent on noncounseling activities (ASCA, ; Burnham & Jackson, ); and (f) limited administrative awareness (Lieberman, ). Factors identified as having a positive relationship with counselors’ programmatic service delivery include job satisfaction (Pyne, ), leadership practices (Shillingford & Lambie, ), school counselor–principal relationship and advocacy skill (Clemens, Milsom, & Cashwell, ), and self‐efficacy and outcome expectancy (Clark, ; Scarborough & Culbreth, ). This study builds on existing research and examines a hypothesized theoretical model depicting the contribution of practicing school counselors’ ( N = 693) self‐efficacy (Bodenhorn & Skaggs, ) to the frequency of their programmatic service delivery (Scarborough, ).…”
mentioning
confidence: 99%
“…On the other hand, as described in the previous section, those guidance personnel are employed with a low salary, short-term contracts, blurred job descriptions and diverse job titles. It is not difficult to imagine, regardless of what qualifications guidance personnel possess, that the blurring of roles and responsibilities will result in high stress, low job satisfaction (Bardhoshi, Schweinle, & Duncan, 2014;Wilkerson & Bellini, 2006), and ultimately turnover intentions (Clemens, Milsom, & Cashwell, 2009).…”
Section: Implications For Guidance and Counselling Services In Primarmentioning
confidence: 99%